(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2024)
A pot experiment was conducted to study the impacts of two types of organic manure on the growth parameters and status of nutrients of red amaranths raised in the manipulated soils obtained by mixing acid and calcareous soils at 3:1 ratio. The experiment was carried out using control, cow dung (3, 6 and 9 t/ha) and poultry manure (2, 4 and 6 t/ha). The results showed that the best plant growth occurred in the manipulated soil (control) than individual calcareous and acid soils. The maximum plant height, fresh weight, N, K and P content of plants were found in case of the medium dose of poultry manure T5 (4 t/ha) while the highest rate of cow dung, T3 (9 t/ha) produced the highest dry weight, N, Ca, Cu, Fe, Mn contents of red amaranth among all organic treatments. The observations of this study revealed that soil manipulation obtained by mixing two problem soils (calcareous and acid soil) could be a viable amelioration procedure, while the application of animal manures could boost soil health suggesting that the process of reclamation and application of organic manures acted synergistically. Bangladesh J. Sci. Ind. Res. 59(3), 179-190, 2024